Revisiting the distribution and total amount of nitrogen fixation across the Kuroshio - Takuya Sato; Takuhei Shiozaki; Shota Takino; Kiyotaka Hidaka; Tamaha Yamaguchi; Daiki Ito; Daisuke Ambe; Sayaka Sogawa; Takashi Setou; Yugo Shimizu; Taketoshi Kodama; Kazutaka Takahashi (Limnology and Oceanography Letters)
Abstract The Kuroshio Current, a western boundary current in the North Pacific Ocean, is regarded as a hotspot of nitrogen fixation that drives marine primary productivity and biogeochemical cycles. However, this assumption is based on limited, spatiotemporally biased data. We curated nitrogen fixation data and applied a generalized additive model to revisit the distribution and total amount of nitrogen fixation in the Kuroshio region. We found a substantial spatial variation, with lower nitrogen fixation in southern Japan and higher rates in the more upstream areas. These variations were explained by nitrate concentration, sea surface temperature, and the distance along the Kuroshio from its origin. We calculated the total nitrogen fixation for the Kuroshio region to be approximately half of the previous estimate. This study provides a more precise estimate of the regional nitrogen fixation and highlights its biogeochemical importance in the Kuroshio region and the western North Pacific Ocean.